HIGH PERFORMANCE FAULT SIMULATION FOR DIGITAL SYSTEMS - Hahanov, Vladimir; Krivoulya, Gennadiy; Hahanova, Irina; Melnikova, Olga; Obrizan, Vladimir (International Journal of Computing, 2014)
Fast backttraced deductive-parallel fault simulation method oriented on processing of complex digital devices containing hundreds of thousand equivalent gates is offered. Data structures and algorithms for method realization are described.